2022
DOI: 10.1186/s12967-022-03616-z
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle sodium content in patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Background Muscle fatigue and pain are key symptoms of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). Although the pathophysiology is not yet fully understood, there is ample evidence for hypoperfusion which may result in electrolyte imbalance and sodium overload in muscles. Therefore, the aim of this study was to assess levels of sodium content in muscles of patients with ME/CFS and to compare these to healthy controls. Methods Six f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Positive studies: oxidative and nitrosative stress, mitochondrial and bioenergetic dysfunction, as reviewed in detail elsewhere (197). Decreased muscle mass action potential (M-wave amplitude and duration) (198) and impaired energy metabolism (201). Disturbed muscle membrane function in motor units, demonstrated by nerve conduction studies (199), and possibly secondary to autonomic dysfunction (200).…”
Section: Muscle Abnormalitiesmentioning
confidence: 99%
“…Positive studies: oxidative and nitrosative stress, mitochondrial and bioenergetic dysfunction, as reviewed in detail elsewhere (197). Decreased muscle mass action potential (M-wave amplitude and duration) (198) and impaired energy metabolism (201). Disturbed muscle membrane function in motor units, demonstrated by nerve conduction studies (199), and possibly secondary to autonomic dysfunction (200).…”
Section: Muscle Abnormalitiesmentioning
confidence: 99%
“…In line with this, histological studies of muscles in PCS revealed capillary injury and rarefication, mitochondrial changes, and inflammation [25,26]. A MRI study revealed higher sodium content in muscles of ME/CFS patients compared to healthy controls and a correlation with HGS suggesting impaired function of ion transport presumably due to hypoperfusion [27].…”
Section: Discussionmentioning
confidence: 82%
“…A number of studies have pointed out the dysfunction of skeletal muscles in ME/CFS, as well as changes in the ME/CSF muscle on the molecular, 34 organelle, 213,214 cellular, 34,215 and tissue 216,217 levels. These include the phenotype of skeletal muscle cells, excitation–contraction cycle, biogenesis of mitochondria, 34 redox status, 214 bioenergetic function, 218 oxidative and nitrosative stress management, metabolic activities, 33 gene expression, protein synthesis, electrolyte content, 219 ss2‐adrenergic receptor function, 32 acid handling, 220 membrane function, 221 etc. The specific skeletal muscle‐derived metabolomic plasmatic profile opens a window of opportunity for biomarker identification.…”
Section: Perspectives: Where We Are Looking and Where We Might Lookmentioning
confidence: 99%